Tinjauan Etis Teologis Dampak Pelaksanaan Upacara Saur Matua di Desa Simaung-Maung Dolok Kecamatan Tarutung Kabupaten Tapanuli Utara - Tefilla Diatessaron Tambunan (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
The purpose of this study was to examine the impact of the implementation of the Saur Matua ceremony in Simaung-Maung Dolok Village, Tarutung District, North Tapanuli Regency from a theological ethical perspective. The method used in this study is a qualitative method with a phenomenological approach. Data were collected through observation and interviews with fourteen informants consisting of ten community members, two traditional leaders, and two religious leaders. The types of data obtained were primary and secondary. This study focuses on the economic impact caused by the Saur Matua ceremony and how it is viewed through the principles of theological ethics. The results of the study indicate that the implementation of the Saur Matua ceremony often has a significant economic impact on families and affects financial well-being. Based on the theological ethical perspective, in the implementation of the Saur Matua ceremony, adjustments are needed so that its implementation can be in line and in harmony with Christian teachings regarding the values ​​of love, truth, justice and simplicity. Saur Matua must be seen as an integral part of the Batak Toba cultural identity, but in its implementation it must be adjusted to Christian values ​​in order to create a balance between cultural preservation and religious teachings.